Differences in Image Quality after Three Laser Keratorefractive Procedures for Myopia. Issue 2 (29th December 2021) - Sarkar, Samrat; Devi, Preetirupa; Vaddavalli, Pravin Krishna; Reddy, Jagadesh C.; Bharadwaj, Shrikant R.
Abstract : SIGNIFICANCE: Psychophysical estimates of spatial and depth vision have been shown to be better after bilateral ReLEx small-incision lenticule extraction (SMILE) refractive surgery for myopia, relative to photorefractive keratectomy (PRK) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK). The present study provides the optical basis for these findings using computational image quality analysis. PURPOSE: This study aimed to compare longitudinal changes in higher-order wavefront aberrations and image quality before and after bilateral PRK, FS-LASIK, and SMILE refractive procedures for correcting myopia. METHODS: Wavefront aberrations and image quality of both the eyes of 106 subjects (n = 40 for FS-LASIK and SMILE and n = 26 for PRK) were determined pre-operatively and at 1-week, 1-month, 3-month, and 6-month post-operative intervals using computational through-focus analysis for a 6-mm pupil diameter. Image quality was quantified in terms of its peak value and its interocular difference, residual defocus that was needed to achieve peak image quality (best focus), and the depth of focus. RESULTS: The increase in root mean squared deviations of higher-order aberrations post-operatively was lesser after SMILE (1-month visit median [25th to 75th interquartile range], 0.34 μm (0.28 to 0.39 μm]) than after PRK (0.80 μm [0.74 to 0.87 μm]) and FS-LASIK (0.74 μm [0.59 to 0.83 μm]; P ≤ .001), all relative to pre-operative values (0.20 μm [0.15 to 0.30 μm]). The peak image quality dropped and its interocular difference increased, best focus shifted myopically by 0.5 to 0.75 D, and depth of focus widened significantly after PRK and FS-LASIK surgeries, all relative to pre-operative values ( P < .001). All these changes were negligible but statistically significant in a minority of instances after SMILE surgery ( P ≥ .01). CONCLUSIONS: Although all three refractive surgeries correct myopia, the image quality and its similarity between eyes are better and closer to pre-operative values after SMILE, compared with FS-LASIK and PRK. These results can be explained from the underlying increase in higher-order wavefront aberrations experienced by the eye post-operatively.